2020
DOI: 10.1042/cs20191028
|View full text |Cite
|
Sign up to set email alerts
|

Myriocin and d-PDMP ameliorate atherosclerosis in ApoE−/− mice via reducing lipid uptake and vascular inflammation

Abstract: Sphingolipids have been implicated in the etiology of atherosclerosis. The commonly used sphingolipid inhibitors, myriocin (a ceramide inhibitor) and d-PDMP (d-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol, a glycosphingolipid inhibitor), have shown therapeutic potential but their efficacy and their underlying mechanisms remain unclear. Here, apolipoprotein E-deficient (apoE−/−) mice were fed a high-fat diet (HFD) and treated with a control, myriocin, d-PDMP, or atorvastatin for 12 weeks. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…In addition, ceramides are one of the structural components of LDL [22] that participates multiple pathological processes in atherosclerosis. Besides, our team also confirmed inhibition of ceramide synthesis could reduce lipid deposition and inflammatory response in vascular wall of ApoE-/-mice so as to delay progression of atherosclerosis [23].…”
Section: Laa Cerebrovascular Diseasesupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, ceramides are one of the structural components of LDL [22] that participates multiple pathological processes in atherosclerosis. Besides, our team also confirmed inhibition of ceramide synthesis could reduce lipid deposition and inflammatory response in vascular wall of ApoE-/-mice so as to delay progression of atherosclerosis [23].…”
Section: Laa Cerebrovascular Diseasesupporting
confidence: 52%
“…In a word, our study found ceramide molecules were increased in LAA cerebrovascular disease. Most patients in the LAA cerebrovascular disease group had been treated with statins to reduce cholesterol and LDL, but they still suffered from stroke.Animal experiments of our team showed that myriocin's inhibitory effect on atherosclerosis was independent of LDL [23]. Therefore, sphingolipids represented by ceramides may have a pathogenic effect on LAA cerebrovascular disease and may be potential therapeutic targets, especially for those with poor therapeutic effects with statins.…”
Section: Laa Cerebrovascular Diseasementioning
confidence: 95%
“…Such myriocin-induced, hormesislike stress responses have been demonstrated in Caenorhabditis elegans [85] and recently Myr treatment, along with RNAi knockdown or mutation of the serine palmitoyltransferase gene, were shown to increase lifespan in C. elegans [86]. Finally, a growing body of data show that Myr treatment reduces the severity of age-related diseases in mice and rats: low dose Myr treatment lowers atherosclerosis and cardiac impairment [87][88][89][90] and reduces risk factors for metabolic syndrome, obesity, diabetes and cancer [91][92][93][94][95]. Myr also reduces amyloid beta and tau hyperphosphorylation in a mouse model of Alzheimer's disease [96] and has therapeutic effects on other neurodegenerative diseases [97,98].…”
Section: Discussionmentioning
confidence: 95%
“…Like rapamycin, myriocin was initially studied for its immunosuppressive activity produced at high dosages [19]. And like rapamycin, lower doses of myriocin have been shown to ameliorate age-related diseases [90, 91, 98, 108]. While humans might not tolerate long-term use of myriocin-like compounds, understanding how they enhance physiological functions and lifespan in model organisms by lowering multiple amino acid pools, could uncover new avenues for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Thermozymocidin also known as Myriocin is an irreversible and high affinity inhibitor of SPT, an enzyme involved in up-regulation in de novo synthesis of ceramide that has therapeutic potential against diabetes, ATS and hepatic steatosis by decresing ceramide levels [86]. In humans treatment with Myriocin did not changed the amount of LDL particles or TG, but rather it changed the composition of LDL particles, especially the concentration of SM [87].…”
Section: Myriocinmentioning
confidence: 99%